Dismissed or Acclaimed for Breaking Norms: The Discursive Positioning of Young Active Citizens in Czech Online Media - Kárníková, Lydie (Javnost-The Public, 2024)
Despite new affordances available since the mainstreaming of digital media in countries with high levels of internet connectivity, young actors in teenage years are a group whose involvement in social and political affairs remains constrained by prevailing stereotypes regarding the social role of youth and acceptable forms of civic engagement. This paper explores the discourse on youths’ active citizenship found in Czech online media outlets, conceptualised as adult-governed spaces. Considering age as a significant exclusionary category in approaches to citizenship, the discursive construction of young active Czech citizens is studied on six concrete local actors and analysed via two types of relational positioning: (1) intra-generational (youth-to-youth) and (2) inter-generational (youth-to-adult). Media representations reveal normative expectations of youth as political actors that range from a refusal to recognise their participation to acclaiming them for it. Depending on the intersection of the actors’ agendas, their personal profiles, and the political orientation of the media outlets, the media depict the actors either negatively as deviant or positively as exceptional, reflecting contemporary ideo-political conflicts in Czechia. The paper concludes that the young age of the actors serves as an amplification factor for discreditation of a counter-attitudinal political agenda.